Elucidating the Electronic Structure and Magnetic and Conducting Properties of μ-oxo Mn-Phthalocyanine [Mnpc(Cn)]2o Complex - Cardenas-Jiron, G; Montenegro-Pohlhammer, N (American Chemical Society, 2019)
The μ-oxo phthalocyanine dimer complex [Mn(Pc)(CN)]2O has been characterized as the first single-component molecular conductor exhibiting magnetoresistance at room temperature. Herewith, we report a detailed study of the electronic structure and the magnetic and conducting properties of this μ-oxo MnPc dimer complex. A combined strategy of wave-function-based quantum chemistry calculations on the complex and plane-wave-based periodic calculations on the crystal has been employed together with semiclassical Boltzmann transport theory calculations. Our results provide information about the ligand field parameters of the Mn ions, clarify their spin states on the [Mn(Pc)(CN)]2O complex, and explain the temperature dependence of both the magnetic susceptibility and the effective magnetic moment, taking into account the presence of excited low-lying states with S = 2 and weak intermolecular magnetic interactions, as key ingredients of the magnetic behavior. The analysis of the density of states of the low-spin and high-spin density functional theory + U magnetic solutions and their respective temperature dependence of the electric resistivity give some clues about the conducting properties and the negative magnetoresistance reported for this system. © 2019 American Chemical Society.